HYDROGEOMORPHOLOGIC ANALYSIS OF LAND AREA - Karel KUDRNA; Marie ŠINDELÁŘOVÁ (Journal of Central European Agriculture, 2010)
In connection with conception of Unitary System of Agricultural, Forest and Water Management, there was necessary to explain relations between stationary and dynamic elements of land area. Knowledge of symmetry of structure of springs of underground waters then led to further explanation of principles which enabled to define land area as a formation making up a hydrogeomorphologically closed system. That is why, in the presented work, relation between a stationary and a dynamic component of land area – geomorphology of area and hydrologic circuit, which determine the state and development of land area in the biosphere, are being solved.